Systematic Review and Meta-analysis of Randomized Controlled Trials of Paclitaxel-Coated Balloon Angioplasty in the Femoropopliteal Arteries: Role of Paclitaxel Dose and Bioavailability. (April 2016) - Katsanos, Konstantinos; Spiliopoulos, Stavros; Paraskevopoulos, Ioannis; Diamantopoulos, Athanasios; Karnabatidis, Dimitris
Purpose: To provide a qualitative analysis and quantitative synthesis of randomized controlled trials (RCTs) investigating paclitaxel-coated balloons (PCBs) in the femoropopliteal artery.Methods: PubMed, EMBASE, AMED, Scopus, CENTRAL, online content, and abstracts from international meetings were last screened in April 2015 for eligible RCTs using the PRISMA selection process. Risk of bias was assessed using the Cochrane Collaboration's tool, and quality of evidence was evaluated with the GRADE system. Outcome measures included late lumen loss (LLL) at 6 months and event rates of major limb amputations, binary lesion restenosis, and target lesion revascularization (TLR). Pooled treatment effects were analyzed in a random effects model to account for clinical heterogeneity; the outcomes are presented as the rate ratios (RRs) and their 95% confidence intervals (CIs). Extensive meta-regression was performed to analyze potential confounders. The review was registered in the PROSPERO database (CRD42015023938; www.crd.york.ac.uk/PROSPERO ).Results: Eleven RCTs with 1609 subjects (1403 claudicants and 206 patients with critical limb ischemia) with medium-length femoropopliteal lesions (mean range 5.1–11.9 cm) were included. There was consistently high-quality evidence supporting the clear superiority of PCBs in terms of reduced LLL (mean difference −0.89 mm, 95% CI −1.14 to −0.64, p<0.001), less binary restenosis (RR 0.47, 95% CI 0.37 to 0.61, p<0.001), and fewer TLR events (RR 0.33, 95% CI 0.22 to 0.49, p<0.001). Major amputations were rare in both active and control arms (pooled event rate: 0.7%, 95% CI 0.3% to 1.2%). Results were stable across all potential risk modifiers and in the presence of stents as well. There was high-quality evidence that the dose of paclitaxel was related to the magnitude of the treatment effect; standard dose (3.0-μg and 3.5-μg) PCBs were significantly more effective compared with low-dose 2-μg PCB in reducing both restenosis (RR 2.1, 95% CI 1.2 to 3.4, p<0.001) and TLR (RR 2.5, 95% CI 1.9 to 3.8, p<0.001).Conclusion: PCBs reduce by more than half the rates of restenosis and TLR in the femoropopliteal artery regardless of stent placement. Biologic effect size may vary according to paclitaxel bioavailability.